Enhancing Competitive Advantage of SMEs Through Strategic Partnership and Entrepreneurial Orientation in the Upstream Oil and Gas Sector: A Case Study of Rokan Block, Indonesia - Nabaga, Tameng; Hendriani, Susi; Samsir, S.; Kamaliah, K. (Journal of Ecohumanism, 2025)
This study examines the role of strategic partnerships and entrepreneurial orientation in enhancing the competitive advantage of Small and Medium Enterprises (SMEs) operating within the Rokan Block upstream oil and gas sector in Indonesia. Unlike previous studies that primarily focus on general SME competitiveness, this research specifically explores the interplay of strategic collaboration and entrepreneurial capabilities in a resource-intensive industry. Employing the Resource-Based View (RBV) and Generic Strategy frameworks, this study highlights how capability development and organizational learning mediate the relationship between partnership programs and competitive advantage. Using a Structural Equation Modeling Partial Least Squares (PLS-SEM) approach, data from SMEs participating in Local Business Development (LBD) initiatives were analyzed. The findings indicate that strategic partnerships significantly impact human resource capabilities, organizational learning, and ultimately, competitive advantage. This study contributes to the literature by integrating strategic management and entrepreneurship theories in the context of SMEs within the oil and gas industry, offering novel insights into sector-specific competitive strategies. Employing the Resource-Based View (RBV) and Generic Strategy frameworks, this research highlights how capability development and organizational learning mediate the relationship between partnership programs and competitive advantage. Using a Structural Equation Modeling.